أهمية الدراسات المرورية في مشاريع إنشاء طرق جديدة، دراسة حالة طريق أبو غار - قيس صاحب كريم (Journal of Engineering and Sustainable Development, 2010)
The increase in traffic movement on the land of dirt is a strong indication of the need to create a new highway. The case study was selected is Nasiriyah-Abu Ghar–Busayyah , which is dirt road. It is observed the increasing of vehicle traffic that using it by increasing its importance in the transport of construction materials from the quarries of Abu Ghar to the provinces of Iraq. Because this road is the temple and with low level of service, then it has needed to develop a design fits its importance and intensity of traffic of heavy vehicles and trucks those carrying construction materials. For more information on these generating and destination point, we made surveys by asking questions to users at counting points. We have also surveys of the current traffic volumes and future traffic volume adoption with (20 years).It was adopted (Highway Capacity Manual) in the analytical calculations to evaluate the proposed design, which developed under a design guide for roads issued by the General Authority for Roads and Bridges.